PEMBERIAN EDUKASI KEPADA MASYARAKAT DESA KIRINGAN DALAM MENERAPKAN PROTOKOL KESEHATAN MENURUT PASAL 12 PERATURAN BUPATI BOYOLALI NOMOR 49 TAHUN 2020 TENTANG PENERAPAN DISIPLIN DAN PENEGAKAN HUKUM PROTOKOL KESEHATAN SEBAGAI UPAYA PENCEGAHAN DAN PENGENDALIA - IQBAL FAJRIYANTO; UNNA RIA SAFITRI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Corona Virus Disease 2019 (COVID-19) is an infectious disease that is caused by one type of coronavirus, namely the SARS-CoV-2 virus which can cause shortness of breath to severe pneumonia, and can even cause death. Therefore, from the current problems, especially for residents of Kiringan Village in places of worship, it is necessary to provide an understanding in order to comply with health protocols and prevent the presence of the corona virus. the author formulates a problem, namely how to attempt to implement discipline and law enforcement of health protocols based on Article 12 of Regent Regulation Number 49 of 2020 concerning Places of Worship. The method used in this research is juridical empirical and the type of research used is a qualitative descriptive approach. So that the author in an effort to enforce the health protocol carried out several activities including providing health protocol education to the takmir of the Al Hidayah Kiringan mosque and to village youths and mosques in Sidodadi Village about spraying